ANALISIS KINERJA RUAS-RUAS JALAN LINGKUNGAN DENGAN MODEL PEMBEBANAN LALU LINTAS MENGGUNAKAN EMME 3.4.1 (STUDI KASUS : KABUPATEN SUKAMARA, KALIMANTAN TENGAH) - Syahidan, Ahmad Harisb januar; Maulana, Reza; Riyanto, Bambang (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Kabupaten Sukamara is a currently growing Kabupaten, especially Kecamatan Balai Riam and Kecamatan Permata Kecubung, but the location is difficult to reach and can be said isolated. One of the aspect that can improve and develop Kabupaten Sukamara is transportation, because the transportation facilities and infrastructure that exist currently is very low in Kabupaten Sukamara, in this case, especially the road which connects the villages because the lack of road development as a rural access. The methodology used for analyze the performance of the road is by calculate the number of trip generation based on the population of study area based on method developed by the Ministry of Public Works for planning transportation of urban road which belong to the small town category. The next step is to analyze the amount of trip that generates Origin Destination Matrice (OD) by using Double Constrain Gravity method (DCGR), assign OD matrice to the road network by using EMME 3.4.1 and calculate the road capacity,then calculate and analyze volume capacity ratio (VCR) based on the assignment result and the road capacity calculation. By determining the 20 year plan, the prediction of trip generation of Kabupaten Sukamara is 235.023 people/day. Based on OD matrice, can be known that the closer the distance trip, the greater the trip that occur and vice versa. From the calculation, the capacity of the collector road is 1.197 smp/hour, local road is 856 smp/hour and small road is 838 smp/hour. From the assignment result, the largest trip volume is 314 smp/hour and the smallest is 1 smp/hour, so the largest VCR value is 0,279 which means VCR < 0,8 for every road that connects the villages. Therefore, the performance condition of the entire road that connects the villages can be concluded stable/safe.